Coordination Frictions and The Financial Crisis - Pieter A. Gautier (Tinbergen Institute, 2009)
In this note I argue that the desirability of fiscal policy in response to the current crisis depends on whether one views the current crisis as a temporary deviation from a unique equilibrium or as a bad equilibrium out of multiple equilibria. The paper presents a simple Diamond (1982) type of model where firms must find an (investment) bank to finance their projects and the investment banks sell risky assets to get capital from investors. Due to coordination frictions, the economy can get stuck in an inefficient low-trade equilibrium. Finally, I briefly discuss some of the policies that have recently been put forward to stimulate the economy in the context of this model.
Keywords: E44; E62; J64; 330; financial crisis; coordination frictions; macroeconomic complementarities; search frictions; Finanzkrise; Internationaler Finanzmarkt; Marktmechanismus; Finanzintermediation; Asymmetrische Information; Suchtheorie; Theorie